Frontline healthcare workers' experiences with personal protective equipment during the COVID-19 pandemic in the UK: a rapid qualitative appraisal. Issue 1 (20th January 2021) - Hoernke, Katarina; Djellouli, Nehla; Andrews, Lily; Lewis-Jackson, Sasha; Manby, Louisa; Martin, Sam; Vanderslott, Samantha; Vindrola-Padros, Cecilia
Abstract : Objectives: To report frontline healthcare workers' (HCWs) experiences with personal protective equipment (PPE) during the COVID-19 pandemic in the UK. To understand HCWs' fears and concerns surrounding PPE, their experiences following its guidance and how these affected their perceived ability to deliver care during the COVID-19 pandemic. Design: A rapid qualitative appraisal study combining three sources of data: semistructured in-depth telephone interviews with frontline HCWs (n=46), media reports (n=39 newspaper articles and 145 000 social media posts) and government PPE policies (n=25). Participants: Interview participants were HCWs purposively sampled from critical care, emergency and respiratory departments as well as redeployed HCWs from primary, secondary and tertiary care centres across the UK. Results: A major concern was running out of PPE, putting HCWs and patients at risk of infection. Following national level guidance was often not feasible when there were shortages, leading to reuse and improvisation of PPE. Frequently changing guidelines generated confusion and distrust. PPE was reserved for high-risk secondary care settings and this translated into HCWs outside these settings feeling inadequately protected. Participants were concerned about differential access to adequate PPE, particularly for women and Black, Asian and Minority Ethnic HCWs. Participants continued delivering care despite the physical discomfort, practical problems and communication barriers associated with PPE use. Conclusion: This study found that frontline HCWs persisted in caring for their patients despite multiple challenges including inappropriate provision of PPE, inadequate training and inconsistent guidance. In order to effectively care for patients during the COVID-19 pandemic, frontline HCWs need appropriate provision of PPE, training in its use as well as comprehensive and consistent guidance. These needs must be addressed in order to protect the health and well-being of the most valuable healthcare resource in the COVID-19 pandemic: our HCWs.